2008
DOI: 10.1074/jbc.m708362200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Cathepsin B Improve Memory and Reduce β-Amyloid in Transgenic Alzheimer Disease Mice Expressing the Wild-type, but Not the Swedish Mutant, β-Secretase Site of the Amyloid Precursor Protein

Abstract: Elucidation of A␤-lowering agents that inhibit processing of the wild-type (WT) ␤-secretase amyloid precursor protein (APP) site, present in most Alzheimer disease (AD) patients, is a logical approach for improving memory deficit in AD. The cysteine protease inhibitors CA074Me and E64d were selected by inhibition of ␤-secretase activity in regulated secretory vesicles that produce ␤-amyloid (A␤). The regulated secretory vesicle activity, represented by cathepsin B, selectively cleaves the WT ␤-secretase site b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
218
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(240 citation statements)
references
References 47 publications
14
218
0
1
Order By: Relevance
“…To explore this possibility, we inhibited lysosomal proteases with E64d and pepstatin A, which resulted in enhanced accumulation of intralysosomal Aβ. Since E64d and pepstatin A are also β-and γ-secretase inhibitors, respectively, 45,46 we found an overall decrease in cytosolic Aβ (data not shown). These results are in agreement with the conception that at least some lysosomal degradative capacity was still present under hyperoxia.…”
Section: Discussionmentioning
confidence: 77%
“…To explore this possibility, we inhibited lysosomal proteases with E64d and pepstatin A, which resulted in enhanced accumulation of intralysosomal Aβ. Since E64d and pepstatin A are also β-and γ-secretase inhibitors, respectively, 45,46 we found an overall decrease in cytosolic Aβ (data not shown). These results are in agreement with the conception that at least some lysosomal degradative capacity was still present under hyperoxia.…”
Section: Discussionmentioning
confidence: 77%
“…Intraperitoneal administration of pepstatin A has been shown to be beneficial for experimental colitis and bone mineralization (101,102), but it needs to be determined whether intracerebroventricular administration of the inhibitor can mitigate NPC pathology. Given the evidence that selective cathepsin B inhibitor can reduce brain A␤ levels/ deposition and improve cognitive behavioral deficits in animal models of Alzheimer disease (72,103), it is likely that the availability of rather selective and potent cathepsin D inhibitors that can cross the blood-brain barrier may provide a new therapeutic opportunity in the treatment of NPC pathology.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Our previous work in transgenic AD mice showed that deleting the cathepsin B gene or treating them with E64d (oral administration) causes major reductions in brain Ab, brain amyloid plaque, and improves memory deficits. 15,17,70,71 Thus, treating TBI patients with a cathepsin B inhibitor may also reduce the subsequent long-term risk of AD.…”
Section: E64d Improves Traumatic Brain Injurymentioning
confidence: 99%